Before Its Time: Public Perception of Disability Rights, the Americans with Disabilities Act, and the Future of Access and Accommodation - Mary Johnson (Washington University Journal of Law & Policy, 2007)
The ADA is not only a law in which economic considerations were allowed to determine civil rights, it was also a major rights law passed with virtually no public scrutiny. After its passage, anti-disability rights groups quickly moved to weaken its protections by publicly ridiculing its provisions. Unlike other civil rights laws, the ADA defined those who were to be granted its protections, and opponents focused on this, taking aim at those they felt did not deserve its protections. The concepts underlying disability rights were not widely understood by the public, and as ADA cases came before judges it was clear that the courts as well had little understanding of the principles upon which the law is based. This proved particularly to be the case when courts attempted to discern who qualified for the law’s protections in the thinking of those who framed the law. But it has become increasingly clear, beginning with the Supreme Court’s rulings in 1999, that the disability rights movement’s concept of “disability” and many of the law’s core concepts have simply not permeated public consciousness. A law designed to protect all Americans from discrimination on the basis of disability—a law which could make life better for many people— seems truly to have been passed before its time.
Keywords: Discrimination against people with disabilities; Perception; Law -- Interpretation & construction; Handicapped discrimination; Public accommodations; Americans with Disabilities Act of 1990; United States